Legal Analysis of Criminal Child with Mental Retardation (Study of Rantauprapat State Court Decision No. 18/PID.SUS/ANAK/2016/PN-RAP) - Irsyam Risdawati; Marice Simarmata; Muhammad Juang Rambe; T. Riza Zarzani; Iwan Rohman Harahap (Budapest International Research and Critics University, 2022)
The perpetrators of criminal acts today are not only dominated by adults, but children also have a great potential to commit criminal acts, even children who are abnormal or mentally retarded can commit crimes as known in the Rantauprapat District Court Decision Number: 18/Pid.Sus-Child. /2016/PN-Rap. This research was conducted normatively by discussing doctrines or principles as well as legal synchronization using the approach to legislation. This means that the principles and synchronization of law are used as benchmarks to provide an assessment of the judge's considerations on the sentencing of children with mental retardation in the Rantauprapat District Court Decision Number: 18/Pid.Sus-Anak/2016/PN-Rap. In Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, it is very possible to apply non-penal policies through diversionary restorative justice instruments but this is not done, the judge's policy in providing legal protection to children with mental retardation is carried out through penal policies in the form of criminal imprisonment for 2 (two) years and 7 (seven) months and a fine of Rp. 100,000,000, - (one hundred million rupiah), provided that if the fine is not paid, it will be replaced with work training for 3 (three) months.